A Qualitative Assessment of an Innovative Suicide Prevention and Treatment Approach: Contextual-Conceptual Therapy - Vyas, Amita; Saunders, Breahnna; Nagaraj, Nitasha (Journal of Public Health International, 2020)
Mental health and mental illness is a critical to a person’s overall health. In the United States alone, mental illness effects one in six adults. Furthermore, 40% of those individuals who die of suicide have been diagnosed with a mental health condition or illness. Yet, there is a paucity of research on innovative methods that help prevent suicide. The Contextual-Conceptual Therapy (CCT) approach introduces an innovative way to treat suicide by working to uncover the strengths of the suicidal person and addressing a person’s true self. The CCT approach was developed over the course of 25 years working with more than 16,000 suicidal patients in Seattle, Washington, and is tailored specifically for primary and secondary prevention of suicide. While there has been anecdotal evidence of the effectiveness of the CCT program, the program has yet to be formally evaluated. This qualitative research study aims to understand the impact the CCT approach has had on its clients. Eleven former CCT clients were recruited to participate in semi-structured interviews. Outcomes described by participants included an increase in curiosity and self-efficacy as a means through which to decrease suicide ideation and behavior, and proved to be incredibly powerful in changing long-term outcomes. This qualitative study is a first-step in providing critical insight on suicide prevention for wider dissemination. At a time when adverse mental health and illness is impacting the lives of millions of people, the CCT approach has the potential to address suicide, mental illness and mental health across diverse populations.
Keywords: suicide ideation; suicide; mental health; suicide prevention and treatment; behavioral therapy